2013
DOI: 10.1159/000353454
|View full text |Cite
|
Sign up to set email alerts
|

Companion Diagnostics in Oncology - Current Status and Future Aspects

Abstract: A large number of targeted anticancer drugs are currently under development and most of them will have a companion diagnostic linked to their use. If a diagnostic assay is developed in conjunction with a targeted anticancer drug, such an assay will later end up determining the conditions for the use of the drug after its approval. The assay then becomes a kind of ‘gatekeeper' in relation to which patients should be treated with the drug in question. This ‘gatekeeper' role implies that companion diagnostic assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…When the selective estrogen receptor modulator tamoxifen (Nolvadex, AstraZeneca) was developed for the treatment of advanced breast cancer, and here data on estrogen receptor (ER) status was correlated with treatment outcome. Based on data from a phase II study in patients with advanced stage breast cancer, published in 1976, the investigators concluded: 'A high degree of correlation between response and positive estrogenreceptor assay suggests the value of the diagnostic test as a means to select patients for tamoxifen treatment' (8,9). Despite the fact that this study was published 40 years ago these principles still apply when drug and diagnostic are developed in parallel.…”
Section: Companion Diagnostics In a Historical Perspectivementioning
confidence: 99%
“…When the selective estrogen receptor modulator tamoxifen (Nolvadex, AstraZeneca) was developed for the treatment of advanced breast cancer, and here data on estrogen receptor (ER) status was correlated with treatment outcome. Based on data from a phase II study in patients with advanced stage breast cancer, published in 1976, the investigators concluded: 'A high degree of correlation between response and positive estrogenreceptor assay suggests the value of the diagnostic test as a means to select patients for tamoxifen treatment' (8,9). Despite the fact that this study was published 40 years ago these principles still apply when drug and diagnostic are developed in parallel.…”
Section: Companion Diagnostics In a Historical Perspectivementioning
confidence: 99%
“…The FDA does allow for clinical trials to only include biomarker positive patients, but does not provide a framework for making decisions about clinical trial design [91]. Having such a framework would be important because clinical trial design is the key to determining the type of information that a companion diagnostic can provide: diagnostics that were only used to find a biomarker positive patient population for a particular drug can only function to select patients for treatment and cannot actually predict whether or not a given patient will respond to the drug [92].…”
Section: Companion Diagnosticsmentioning
confidence: 99%
“…Hence, for many drugs, the CDx assays will take up a central role as a kind of 'decisive' stratification factor, both during the different clinical development phases and later after approval when the drug is to be routinely used in the clinic. The assay will then become a kind of 'gatekeeper' in relation to the treatment decision and with this central role in mind the regulatory requirements for CDxs need to be at the same level as for drugs [9]. This is also stressed in the interview with Daniel Hayes where he states that "A bad tumor biomarker test is as bad as a bad drug."…”
mentioning
confidence: 99%
“…In relation to the development of CDx assays, both the analytical and clinical performance needs to be documented carefully using different elements of the drug-diagnostic codevelopment model [9]. With regard to the economic evaluation the same kind of 'standard' does not exist.…”
mentioning
confidence: 99%